The role of nutritional support in the recovery process of patients with acute cerebral circulatory failure - T. V. Novikova; M. V. Chirkova (Лечащий Врач)
Background. The participants of the breakout session "Role of nutritional support in the process of recovery of patients with acute cerebral circulatory failure", organised with the support of Nutricia Company within the framework of the II All-Russian Neurocongress with international participation, held on 10-12 October 2024 in Moscow, discussed the problems and approaches to the recovery of patients with acute cerebral circulatory failure.Conclusion. Close attention of the participants was focused on the issues of adequate replenishment of nutritional needs of the patients' organism, without which rehabilitation is impossible.